2017
DOI: 10.5781/jwj.2017.35.2.2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Interpass Peening on Mechanical Properties in Additive Manufacturing of Ti-6Al-4V

Abstract: Ti-alloys have high specific strength and are widely used for the filed of space aeronautics plant. However, it is difficult to process Ti-Alloys due to its high yield strength and it cannot raise the machining speed because it has a possibility of catching fire while processing. In order to reduce the number of processes for the Ti-alloys, the researches related to Additive Manufacturing(AM) have been actively carried out at the moment. As for the initial stage of AM market related to Ti-alloys, it started to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
2
5
0
Order By: Relevance
“…The preferential direction of elongation for the vertical direction with a decrease in strength is eliminated and isotropic properties are achieved through the grain refinement induced by inter-pass MHP. Similar properties have been reported in Byun et al [13].…”
Section: Tensile Propertiessupporting
confidence: 91%
See 2 more Smart Citations
“…The preferential direction of elongation for the vertical direction with a decrease in strength is eliminated and isotropic properties are achieved through the grain refinement induced by inter-pass MHP. Similar properties have been reported in Byun et al [13].…”
Section: Tensile Propertiessupporting
confidence: 91%
“…Also, the rolling speed reported ranges from 3 to 7 mm/s [7,11], which may increase significantly the production time of the WAAM components. Machine Hammer Peening (MHP) has been previously studied as an alternative to this technology [11][12][13]. It is shown that MHP has the capability of refining the previously columnar β grains and that it can be applied robotically, guaranteeing the flexibility and repeatability required to employ this technology to WAAM components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tool can be easily used with a robotic arm, which offers the possibility of applying cold work to potentially any geometry [23]. Inter-pass MHP was first studied by Byun et al [24]. An average β grain size of 460 µm was obtained, and the α laths size decreased by ~40% from the as deposited condition, which increased the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the issues, additive manufacture (AM) has been developed as a promising technology to fabricate a three-dimensional net-shaped product in a manner of layer-by-layer. The feature of net-shaped can minimize the material waste, which increases the buy-to-fly ratio and subsequently enhances the cost-effectiveness 6,7) . AM can be divided into powder bed fusion (PBF) and directed energy deposition (DED) based on the principle process.…”
Section: Introductionmentioning
confidence: 99%